Effects of Mg on morphologies and properties of hot dipped Zn-Mg coatings - Yao, C.; Wang, Z.; Tay, S.L.; Gao, W. (Elsevier, 2014)
This research aims to study the processing and the properties of hot-dipped Zn-Mg coatings with varying amount of Mg compositions. Zn-Mg coatings with 1 wt.%, 2 wt.%, 3 wt.% and 4 wt.% Mg were produced at 685 degrees C using molten salt furnace with Argon protective gas atmosphere to minimise the oxidation of Mg. Characterisation techniques including X-ray diffraction (XRD) and environmental scanning electron microscope (ESEM) were performed to study the microstructures and phases of the coatings. The results showed that laminar eutectic containing MgZn2 and Zn formed at the grain boundary areas of Zn crystals in Zn-Mg coatings. Accelerated corrosion test methods like electrochemical and salt water immersion tests verified the improved anticorrosion properties of Zn-3 wt.% Mg coating compared with pure Zn coating. A significant enhancement in the microhardness was also observed with the addition of Mg into the coating composition. (C) 2014 Elsevier B.V. All rights reserved.